(untitled) (Research, Society and Development, 2022)
This article makes a discussion about a scientific investigation of the contributions of reading of the science fiction literary genre in the scientific literacy construction of integrated high school students. In this study, it was tried to do an analogy between the reflective reading of science fiction stories by the author Isaac Asimov and the social function of science in modern times, based on the fundamentals of meaningful learning by David Ausubel, of the Science, Technology and Society (STS) movement and the Professional and Technological Education (PTE). The application of the intervention proposal as a contributing element to the achievement of the proposed objectives is highlighted in the results. For this, from a qualitative approach to the data, an action research was adopted as a methodological way. Application of an intervention proposal in this study was stood out as a contributing element to the achievement of the proposed objectives. The results revealed, therefore, the importance of this pedagogic tool for the construction of scientific literacy of students in the initial years of integrated education.